The Optimal Winter Cropping Pattern Maximizing Total Production Value in Hama Governorate (Damascus University Journal of agriculture sciences, 2022)
The research was conducted in Hama Governorate, second stability zone, during agricultural season (2017/2018), based on primary data for a simple random sample of 400 farmers, and secondary data for the time series (2004-2018). Aimed to reach optimal winter cropping pattern which Maximizes total agricultural production value, and comparing it with the prevailing winter cropping pattern during three agricultural seasons of (2016-2018) using Operations Research methodology, Linear Programming manner, Simplex method. The results showed that for reaching to optimal winter cropping pattern that maximizes total production value of winter crops in the research area, within the constraints of available water resources for irrigation the winter crops, and available winter cropping area, while preserving diversity of production from most dominant winter crops in the research area, requires expansion in cultivation the following winter crops: wheat, cumin, beans, barley, golden winter onions, chickpeas, anise, garlic, and spring potatoes, at rates of (187%), (140%), (118%), (73%), (67%). ), (62%), (55%), (45%), (41%) respectively; of their average prevailing areas during the period (2016-2018). Also; The comparison results with prevailing winter cropping pattern in research area showed that optimal winter cropping pattern that maximizes total production value, achieves an increase in total production value of winter cropping pattern by (109.76%) compared with the production value of prevailing winter cropping pattern, in addition to an increase in the net profit by (109.82%) compared with the net profit of prevailing cropping pattern, Conversely, the optimal winter cropping pattern use more quantities of water by (146.59%), and its production cost is higher by (109.69%) than of cost of prevailing cropping pattern.
Keywords: Operation Research; Liner Programming; Simplex; Optimal Cropping Pattern; Hama